Dopamine Receptor D1 Contributes to Cocaine Epigenetic Reprogramming of Histone Modifications in Male Germ Cells - González, Betina; Gancedo, Samanta N.; Garazatua, Sahira A. Janeir; Roldán, Eduardo; Vitullo, Alfredo D.; González, Candela R. (Frontiers in Cell and Developmental Biology, 2020)
Paternal environmental perturbations, including cocaine intake, can affect the development and behavior of the offspring through epigenetic inheritance. However, the mechanism by which cocaine alters the male germ cells epigenome is almost unexplored. Here, we report that cocaine-treated male mice showed alterations on specific histone post-translational modifications (PTMs) including increased silent chromatin marks H3K9me3 and H3K27me3 and decreased active enhancer and promoter marks H3K27ac and H3K4me3 in isolated germ cells. Also, cocaine increased H3K9ac and H4K16ac levels, involved in the replacement of histones by protamines that take place at round spermatid stage. Cocaine also altered histones H3/H4 epigenetic enzymes by increasing acetyltransferase KAT8/MOF, deacetylase SIRT1 and methyltransferase KMT1C/G9A, and decreasing deacetylases HDAC1/2 and demethylase KDM1A/LSD1 protein levels. Moreover, a pre-treatment with dopamine receptor 1 (DRD1) antagonist SCH23390 (SCH) blocked cocaine effects on H3K4me3, H3K27me3 and H4K16ac epigenetic marks. Interestingly, treatment with SCH-only was able to modify most of the histone marks tested here, pointing to a dopamine role in controlling histone PTMs in germ cells. Taken together, our data suggest a key role for DRD1 in mediating cocaine-triggered epigenetic modifications related to the silencing of gene transcription and the histone-to-protamine replacement that controls chromatin architecture of maturing sperm cells, and pinpoints a novel role of the dopaminergic system in the regulation of male germ cells reprogramming.